Improving the Innovation Capability of Batik SMES Based on Intellectual Stimulation Organizational Supervision and Knowledge Management Accumulated - Marno Nugroho; Sulistyo Suharto; Yuniar Dwi Lestari (Budapest International Research and Critics University, 2022)
This study aims to identify and analyze the effect of intellectual stimulation, organizational supervision, and knowledge management accumulation. The population in this survey is all batik owners in the city of Semarang. The number of samples taken from a population of 100 respondents was determined using the deliberate sampling method and the Lame show formula. The data analysis method used is quantitative analysis using multiple linear regression analysis to determine the value and nature of the influence of the variables studied. Analysis of the impact of organizational supervision on Innovation Capability: From the above analysis, we conclude that the sig value of organizational supervision is 0.03 < 0.05 and the T-Test value is 2.879, which directly impacts organizational supervision on innovation capability. Analysis of the influence of intellectual stimulus on innovation ability: From the above analysis, the T test value of intellectual stimulus is 1.131 we can conclude that there is no direct influence of intellectual stimulation on the ability to innovate. Analysis of the impact of knowledge management accumulation on innovation ability: From the above analysis, it can be obtained the sig value of management accumulation. Since 0.003 < 0.05 and the T test value is 2.199, we can conclude that knowledge management accumulation has a direct impact on innovative ability.